Pengaruh lama reaksi terhadap karakteristik pati modifikasi kimpul (Xanthosoma sagittifolium) secara asetilasi menggunakan asam asetat - Sarlina Palimbong; Karina Bianca Lewerissa; Eirene Putri Cahyani Laia (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Kimpul (Xanthosoma sagittifolium) tubers containing a lot of starch can be processed into modified starch with better characteristics. Reaction time is one factor determining the characteristics of acetylated modified starch. The purpose of this study was to assess the effect of reaction time on the characteristics of modified starch of kimpul tubers by acetylation using acetic acid. The research used a Simple Randomised Complete Design (CRD) with 3 types of treatment and 3 replications, namely 110 minutes, 115 minutes, and 120 minutes. Data analysis used One Way ANOVA followed by Duncan’s test with 5 % confidence interval. The research began with the extraction of kimpul starch, modification of starch by acetylation, and then testing the degree of substitution, swelling power, solubility, and clarity of the paste. The length of the reaction will increase the degree of substitution (0,2400-0,6460) but tends to decrease the solubility (0,0171-0,0123 %) and clarity of starch paste (0,852-0,915) and produce a stable starch (2,4996-23535 g/g). Acetylated kimpul tuber starch with a reaction time of 110 minutes can be applied as a thickener for liquid food.